Protocol for systematic review: patient decision aids for total hip and knee arthroplasty decision-making - Pacheco-Brousseau, Lissa; Charette, Marylène; Stacey, Dawn; Poitras, Stéphane (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background Total hip and knee arthroplasty are a highly performed surgery; however, patient satisfaction with surgery results and patient involvement in the decision-making process remains low. Patient decision aids (PtDAs) are tools used in clinical practices to facilitate active patient involvement in healthcare decision-making. Nonetheless, PtDA effects have not been systematically evaluated for hip and knee total joint arthroplasty (TJA) decision-making. The aim of this systematic review is to determine the effect of patient decision aids compared to alternative of care on quality and process of decision-making when provided to adults with hip and knee osteoarthritis considering primary elective TJA. Methods This systematic review will follow the Cochrane Handbook for Systematic Reviews. This protocol was reported based on the PRISMA-P checklist guidelines. Studies will be searched in CINAHL, MEDLINE, Embase, PsycINFO, and Web of Science. Eligible studies will be randomized control trial (RCT) evaluating the effect of PtDA on TJA decision-making. Descriptive and meta-analysis of outcomes will include decision quality (knowledge and values-based choice), decisional conflict, patient involvement, decision-making process satisfaction, actual decision made, health outcomes, and harm(s). Risk of bias will be evaluated with Cochrane’s risk of bias tool for RCTs. Quality and strength of recommendations will be appraised with Grades of Recommendation, Assessment, Development and Evaluation (GRADE). Discussion This review will provide a summary of RCT findings on PtDA effect on decision-making quality and process of adults with knee and hip osteoarthritis considering primary elective TJA. Further, it will provide evidence comparing different types of PtDA used for TJA decision-making. This review is expected to inform further research on joint replacement decision-making quality and processes and on ways PtDAs facilitate shared decision-making for orthopedic surgery. Systematic review registration PROSPERO CRD42020171334